Publications from International Organizations on Public Health - Annarita Barbaro (Istituto Superiore di Sanità, 2024)
The Publications from International Organizations on Public Health section includes a wider selection of the most recent publications edited by the main international organizations active in the field of public health, such as: the European Food Safety Authority (EFSA), the Food and Agriculture Organization of the United Nations (FAO), the International Labour Organization (ILO), the Organisation for Economic Co-operation and Development (OECD), the United Nations Educational, Scientific and Cultural Organization (UNESCO), the United Nations Environment Programme (UNEP), the United Nations Programme on HIV/AIDS (UNAIDS), and the World Health Organization (WHO).